Polyolefin composition for drying agent packaging and preparation method thereof

The appearance defects of traditional breathable films are solved by using a specific proportional mixture of low-density polyethylene and linear low-density polyethylene and heavy calcium carbonate of a specific particle size in the breathable film for desiccant packaging, combined with the surface treatment agent coating treatment, and the appearance defects of traditional breathable films are solved. and poor performance problems, polyolefin compositions with high breathability, good mechanical properties and good appearance are achieved.

CN119220011AActive Publication Date: 2024-12-31KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411350285.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

When traditional desiccant packaging, breathable films for improving breathability and mechanical properties, it is difficult to maintain a good product appearance, and appearance defects such as surface bark patterns during stretching and film making are prone to occur.

Method used

Use a specific proportional mixture of low-density polyethylene and linear low-density polyethylene as polyolefin resin, and select heavy calcium carbonate with a specific average particle size to improve breathability by forming pores at the interface of calcium carbonate, while packaging the surface treatment agent Overlaying improves mechanical properties and breathability.

Benefits of technology

The polyolefin composition for desiccant packaging that achieves high breathability, good mechanical properties and good appearance meets the requirements of the desiccant packaging field for breathability, tensile strength and appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062164620000081
    Figure BDA0005062164620000081
  • Figure BDA0005062164620000091
    Figure BDA0005062164620000091
  • Figure BDA0005062164620000092
    Figure BDA0005062164620000092
Patent Text Reader

Abstract

The invention discloses a polyolefin composition for drying agent packaging and a preparation method thereof, and relates to the technical field of modified plastics. The invention provides a polyolefin composition for drying agent packaging. The polyolefin composition comprises the following components in parts by weight: 30-50 parts of polyolefin resin, 35-70 parts of ground calcium carbonate, 0.5-2 parts of an antioxidant and 0.5-2 parts of a processing aid, the polyolefin resin is a mixture of low-density polyethylene and linear low-density polyethylene, the weight ratio of the low-density polyethylene to the linear low-density polyethylene is (1-2): (3-6), the melt flow rate of the low-density polyethylene is 1-15g / 10min under the conditions of 190 DEG C and 2.16 kg according to ISO 1133-1-2011, and the density of the linear low-density polyethylene is 0.93-0.95 g / cm < 3 >; the average particle size D50 of the heavy calcium carbonate is 4-7 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified plastics, in particular to a polyolefin composition for desiccant packaging and a preparation method thereof. Background Art

[0002] Polyolefin breathable membrane is made of polyolefin filling system and stretched to form pores. The interface between resin and inorganic filler forms a through microporous network structure, which allows small molecule water vapor to pass through, but larger droplets cannot, thus having the function of breathability and waterproofing. Polyolefin filling system is usually a combination of polyolefin + heavy calcium carbonate. As a key structural component, polyolefin breathable membrane is widely used in functional packaging such as desiccant packaging, hygiene base film such as diapers, sanitary napkins, etc., medical / industrial protective clothing and other fields.

[0003] The breathable film for desiccant packaging is used in the fields of food, medicine, clothing and luggage. It has built-in silica gel particles or calcium oxide to absorb moisture in the air to keep the scene dry. Different from the breathable film products traditionally used in the fields of sanitary materials and protection, the breathable film for desiccant packaging has the following requirements: (1) The breathable film for desiccant packaging has a higher gram weight to maintain higher mechanical strength, usually above 30gsm; (2) Due to the high thickness of the breathable film for desiccant packaging, appearance defects (surface bark texture) are prone to occur during the stretching film making process; (3) The breathable film for desiccant packaging has ultra-high air permeability, and the air permeability must be greater than 3400g / m 2 · More than 24 hours, so that it can efficiently absorb moisture in the air. Traditional breathable membranes for desiccant packaging meet the requirements through the following two points: first, the material link improves the air permeability and increases the content of inorganic powder; second, the breathable membrane production link improves the air permeability, increases the stretching ratio and increases the number of micropores. However, the preparation of traditional breathable membranes for desiccant packaging will have a great impact on the product appearance, mechanical properties and air permeability, and cannot balance the requirements of the three.

[0004] Therefore, a polyolefin composition for desiccant packaging having high air permeability, good mechanical properties and good product appearance has broad application prospects. Summary of the invention

[0005] Based on this, one of the purposes of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a polyolefin composition for desiccant packaging with high air permeability and good mechanical properties and a preparation method thereof. Another purpose of the present invention is to provide a polyolefin composition for desiccant packaging with good product appearance and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a polyolefin composition for desiccant packaging, comprising the following components in parts by weight: 30-50 parts of polyolefin resin, 35-70 parts of heavy calcium carbonate, 0.5-2 parts of antioxidant, and 0.5-2 parts of processing aid; the polyolefin resin is a mixture of low-density polyethylene and linear low-density polyethylene, and the weight ratio is (1-2): (3-6); the low-density polyethylene has a melt flow rate of 1-15 g / 10 min at 190° C. and 2.16 kg according to ISO 1133-1-2011, and the density of the linear low-density polyethylene is 0.93-0.95 g / cm 3 ; The average particle size D50 of the heavy calcium carbonate is 4-7 microns.

[0007] The polyolefin resin of the present invention selects a mixture of low-density polyethylene and linear low-density polyethylene in a specific ratio, which is more conducive to forming holes at the calcium carbonate interface during the stretching process, thereby improving the air permeability. The present invention selects heavy calcium carbonate with a specific average particle size to enhance the material's ability to form holes at the calcium carbonate / resin interface during the stretching process, thereby further improving the air permeability. At the same time, the selection of heavy calcium carbonate with a specific average particle size of the present invention ensures the mechanical properties of the polyolefin composition for desiccant packaging.

[0008] Preferably, the molecular weight distribution Mw / Mn of the low-density polyethylene is 10-15, and the density of the low-density polyethylene is 0.915-0.925 g / cm 3 .

[0009] Preferably, the molecular weight distribution Mw / Mn of the linear low-density polyethylene is 5-10, and the comonomer of the linear low-density polyethylene is at least one of hexene and octene.

[0010] Preferably, the linear low-density polyethylene has a melt flow rate of 0.5-2.0 g / 10 min at 190° C. and 2.16 kg according to ISO 1133-1-2011.

[0011] The inventors found in actual experiments that the polyolefin resin of the present invention, which is a mixture of low-density polyethylene and linear low-density polyethylene in a specific ratio, can give the material good appearance uniformity during the stretching process.

[0012] The density test of the low-density polyethylene and linear low-density polyethylene described in the present invention adopts the immersion method in the determination of density of non-foamed plastics in GB / T1033.1-2008 plastics, and the weight average molecular weight and number average molecular weight of the low-density polyethylene and linear low-density polyethylene are obtained by gel permeation chromatography (GPC) testing. The ratio of the weight average molecular weight to the number average molecular weight is the molecular weight distribution Mw / Mn. The testing method for the average particle size D50 of the heavy calcium carbonate described in the present invention is the Malvern laser particle size testing method.

[0013] Optionally, the test method for the average particle size D50 of heavy calcium carbonate is as follows: add 3g of filler to 500mL of water, shake in an ultrasonic instrument for 1min, add the dispersed sample, put it into a Malvern laser particle size analyzer, inject the sample for testing, laser wavelength 630nm, scattering angle of particles 90°, test time 300s, correlator: low speed, medium temperature 21, light intensity distribution type, and use CONTIN2 analysis mode.

[0014] Optionally, the weight of the polyolefin resin is 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts or any two of the range values; the heavy calcium carbonate is 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts, 51 parts, 53 parts, 55 parts, 58 parts, 60 parts, 61 parts, 63 parts, 65 parts, 68 parts, 70 parts or any two of the range values; the antioxidant is 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 1.8 parts, 2 parts or any two of the range values; the processing aid is 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 1.8 parts, 2 parts or any two of the range values.

[0015] Optionally, the polyolefin resin is a mixture of low-density polyethylene and linear low-density polyethylene, and the weight ratio is in the range of one or any two of 1:3, 1:4, 1:5, 1:6, 2:3, 2:4, 2:5, 2:6.

[0016] Optionally, the melt flow rate of the low density polyethylene at 190°C and 2.16 kg according to ISO 1133-1-2011 is 1 g / 10min, 2 g / 10min, 2.5 g / 10min, 3 g / 10min, 4 g / 10min, 5 g / 10min, 6 g / 10min, 7 g / 10min, 8 g / 10min, 9 g / 10min, 9.5 g / 10min, 10 g / 10min, 12 g / 10min, 13 g / 10min, 15 g / 10min, or any two of the range values. The molecular weight distribution Mw / Mn of the low density polyethylene is 10, 11, 12, 13, 15, or any two of the range values. The density of the low density polyethylene is 0.915, 0.920, 0.925 g / cm 3 The range value of one or both of them.

[0017] Optionally, the melt flow rate of the linear low-density polyethylene at 190°C and 2.16 kg according to ISO 1133-1-2011 is 0.5 g / 10 min, 0.8 g / 10 min, 1 g / 10 min, 1.5 g / 10 min, 2.0 g / 10 min or any two of the range values. The molecular weight distribution Mw / Mn of the linear low-density polyethylene is 5, 6, 7, 8, 9, 10 or any two of the range values. The density of the linear low-density polyethylene is 0.93 g / cm 3 , 0.935g / cm 3 、0.94g / cm 3 , 0.945g / cm 3 , 0.95g / cm 3 The range value of one or both of them.

[0018] Optionally, the average particle size D50 of the heavy calcium carbonate is in the range of 4 microns, 5 microns, 6 microns, 7 microns or any two of them.

[0019] Preferably, the weight percentage of the polyolefin resin in the polyolefin composition for desiccant packaging is not less than 25%.

[0020] Preferably, the heavy calcium carbonate is heavy calcium carbonate obtained by coating with a surface treatment agent, and the surface treatment agent is at least one of stearic acid, phosphate ester, titanate ester, and aluminate ester; more preferably, the surface treatment agent is phosphate ester.

[0021] Furthermore, the weight of the surface treatment agent is 0.5wt%-2wt% of the weight of the heavy calcium carbonate. Since the added amount of the surface treatment agent is less than 2wt%, the effect of the coating on the particle size of the heavy calcium carbonate before and after coating can be ignored.

[0022] Optionally, the weight of the surface treatment agent is in the range of one or any two of 0.5wt%, 0.7wt%, 0.8wt%, 1wt%, 1.5wt%, 1.6wt%, 1.8wt%, 1.9wt%, 2.0wt% of the weight of the heavy calcium carbonate.

[0023] Preferably, the method for preparing the ground calcium carbonate coated with a surface treatment agent comprises the following steps: preparing activated ground calcium carbonate by a high-speed mixer, matching different high-speed mixer speeds, adding a specific dose of surface treatment agent when the set temperature is reached, and achieving uniform coating of the surface treatment agent under high-speed and high-temperature stirring and mixing.

[0024] Optionally, the high speed mixer has a rotation speed range of 400-600 rpm and a temperature range of 115-125°C.

[0025] Optionally, the heavy calcium carbonate obtained by coating with a surface treatment agent according to the present invention can be prepared by the above method or directly purchased from the market.

[0026] The inventors found in actual experimental processes that when the heavy calcium carbonate is heavy calcium carbonate obtained by coating with a surface treatment agent, the appearance and mechanical properties of the prepared polyolefin composition for desiccant packaging are better. When the surface treatment agent is a phosphate ester, the air permeability can be better improved through interfacial adsorption, and at the same time, the tensile strength of the film can be improved to a certain extent.

[0027] Optionally, the weight of the surface treatment agent is tested by loss on ignition method: the heavy calcium carbonate obtained by coating with the surface treatment agent is first dried at 105-110°C to remove the influence of moisture, and then calcined at 420-470°C for 30-50 minutes. The percentage of weight lost during the calcination stage is the weight percentage of the surface treatment agent.

[0028] Preferably, the weight ratio of the low-density polyethylene to the linear low-density polyethylene is 1:3-5.

[0029] The inventors found in actual experiments that the weight ratio of the low-density polyethylene to the linear low-density polyethylene will further affect the air permeability, mechanical properties and product appearance of the polyolefin composition for desiccant packaging. When the weight ratio of the low-density polyethylene to the linear low-density polyethylene is 1:3-5, the performance of the polyolefin composition for desiccant packaging is better.

[0030] Preferably, the antioxidant is at least one of hindered phenols and phosphites, the processing aid is a lubricant, and the lubricant is at least one of fluorine-containing compounds, polyolefin waxes, low molecular esters, stearates, and amides, such as pentaerythritol stearate, zinc stearate, etc.

[0031] Optionally, the hindered phenol antioxidant includes at least one of 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol ester, bis[β-(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)]hydrazine, and tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl)propionate]pentaerythritol; the phosphite antioxidant includes at least one of bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate, tetrakis(2,4-di-tert-butylphenol)-4,4-biphenyl diphosphite, and tris[2.4-di-tert-butylphenyl]phosphite.

[0032] In addition, the present invention provides a method for preparing the polyolefin composition for desiccant packaging, comprising the following steps: mixing the components in proportion, melt-extruding and granulating to obtain the polyolefin composition for desiccant packaging.

[0033] Preferably, the extruder screw has an aspect ratio of 40:1-52:1, and a processing temperature of 180-220°C.

[0034] Furthermore, the present invention provides an application of the polyolefin composition for desiccant packaging in the field of desiccant packaging. Optionally, the desiccant packaging field includes food desiccant packaging, daily necessities desiccant packaging, clothing desiccant packaging and other fields.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows: the polyolefin resin of the present invention selects a mixture of low-density polyethylene and linear low-density polyethylene in a specific ratio, which is more conducive to forming holes at the calcium carbonate interface during the stretching process, thereby improving the air permeability. The present invention enhances the material's ability to form holes at the calcium carbonate / resin interface during the stretching process by selecting heavy calcium carbonate with a specific average particle size, thereby further improving the air permeability. At the same time, the selection of heavy calcium carbonate with a specific average particle size of the present invention ensures the mechanical properties of the polyolefin composition for desiccant packaging. The inventors found in actual experimental processes that the polyolefin resin of the present invention selects a mixture of low-density polyethylene and linear low-density polyethylene in a specific ratio, which can give the material good appearance uniformity during the stretching process. DETAILED DESCRIPTION

[0036] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.

[0037] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0038] Low-density polyethylene-1 (LDPE-1): melt flow rate 8g / 10min (190℃, 2.16kg), density 0.916g / cm 3 , brand LDPE 722, manufacturer DOW;

[0039] Low-density polyethylene-2 ​​(LDPE-2): melt flow rate 15g / 10min (190℃, 2.16kg), density 0.918g / cm 3 , brand name EXCEED 0015XC, manufacturer ExxonMobil;

[0040] Low-density polyethylene-3 (LDPE-3): melt flow rate 0.75g / 10min (190℃, 2.16kg), density 0.92g / cm 3 , brand LDPE 310E, manufacturer DOW;

[0041] Low-density polyethylene-4 (LDPE-4): melt flow rate 40g / 10min (190℃, 2.16kg), density 0.92g / cm 3 , brand LDPE M1840, manufacturer Yanshan Petrochemical;

[0042] Linear low-density polyethylene-1 (LLDPE-1): melt flow rate 0.9 g / 10 min (190 ° C, 2.16 kg), density 0.94 g / cm 3 , brand LLDPE 4009MC, manufacturer ExxonMobil;

[0043] Linear low-density polyethylene-2 ​​(LLDPE-2): melt flow rate 0.5g / 10min (190℃, 2.16kg), density 0.935g / cm 3 , brand LLDPE ENABLE 3505, manufacturer ExxonMobil;

[0044] Linear low-density polyethylene-3 (LLDPE-3): melt flow rate 1g / 10min (190℃, 2.16kg), density 0.92g / cm 3 , brand LLDPE ENABLE2010PA, manufacturer ExxonMobil;

[0045] High-density polyethylene-1 (HDPE-1): melt flow rate 0.85g / 10min (190℃, 2.16kg), density 0.962g / cm 3 , brand HDPE 5960G, manufacturer DOW;

[0046] HDPE-2: melt flow rate 8g / 10min (190℃, 2.16kg), density 0.958g / cm 3 , brand name HDPE8008, manufacturer: Lanzhou Petrochemical.

[0047] Heavy calcium carbonate-1: average particle size D50 is 4.2 microns, brand AC-72, manufacturer (Lianzhou) Powder Technology;

[0048] Heavy calcium carbonate-2: average particle size D50 is 5.0 microns, brand AC-77, manufacturer Xinrong (Lianzhou) Powder Technology;

[0049] Heavy calcium carbonate-3: average particle size D50 is 6.5 microns, brand AC-64, manufacturer Xinrong (Lianzhou) Powder Technology;

[0050] Heavy calcium carbonate-4: average particle size D50 is 2.5 microns, brand AC-26, manufacturer Xinrong (Lianzhou) Powder Technology;

[0051] Heavy calcium carbonate-5: average particle size D50 is 8.0 microns, brand AC-88, manufacturer Xinrong (Lianzhou) Powder Technology;

[0052] Heavy calcium carbonate-6: The average particle size D50 is 4.9 microns, the brand is OMYACARB 5T, the surface treatment agent used is stearic acid, the manufacturer is OMYA.

[0053] Surface treatment agent-1: phosphate ester, brand RP-98, manufacturer: Maoheng Chemical;

[0054] Surface treatment agent-2: titanate, brand PN-130, manufacturer: Pinning Chemical;

[0055] Surface treatment agent-3: stearic acid, brand stearic acid 181, manufacturer Hunan Chengcheng Oil Chemical;

[0056] Antioxidant: The antioxidant is a composite of commercially available hindered phenol antioxidant 1010 and commercially available phosphite antioxidant 168 in a mass ratio of 1:1. The same commercially available product is used in the parallel examples and comparative examples.

[0057] Processing aid: zinc stearate, commercially available, the same commercially available product was used in the parallel examples and comparative examples;

[0058] Examples 1-12 and Comparative Examples 1-9

[0059] The preparation method of the heavy calcium carbonate coated with the surface treatment agent used in the embodiment and the comparative example comprises the following steps: preparing activated heavy calcium carbonate by a high-speed mixer, the high-speed mixer speed is 500 rpm, matching different high-speed mixer speeds, adding a specific dose of the surface treatment agent when the temperature reaches 120°C, and achieving uniform coating of the surface treatment agent under high-speed and high-temperature stirring and mixing. In the coated heavy calcium carbonate, the weight of the surface treatment agent is 1wt% of the weight of the heavy calcium carbonate.

[0060] Among them, the preparation methods of coated heavy calcium carbonate-1, coated heavy calcium carbonate-2, coated heavy calcium carbonate-3, coated heavy calcium carbonate-4, and coated heavy calcium carbonate-5 in Tables 1 and 2 are as above, among which, coated heavy calcium carbonate-1 is coated with heavy calcium carbonate-1, and so on, which are not described one by one.

[0061] Among them, the surface treatment agent used for coated heavy calcium carbonate-1, coated heavy calcium carbonate-2, coated heavy calcium carbonate-3, coated heavy calcium carbonate-4, and coated heavy calcium carbonate-5 are all surface treatment agent-1: phosphate ester.

[0062] The surface treatment agent selected for coated heavy calcium carbonate-11 is surface treatment agent-2: titanate, and the surface treatment agent selected for coated heavy calcium carbonate-12 is surface treatment agent-3: stearic acid.

[0063] The preparation method of the polyolefin composition for desiccant packaging of the present invention comprises the following steps: mixing the components in proportion, melt extruding and granulating to obtain the polyolefin composition for packaging. The aspect ratio of the extruder screw is 48:1, and the processing temperature is in the range of 200-220°C.

[0064] The embodiments and comparative examples of the polyolefin composition for desiccant packaging of the present invention, the components of the polyolefin composition for desiccant packaging are shown in Table 1 and Table 2.

[0065] Table 1

[0066]

[0067]

[0068]

[0069] Table 2

[0070]

[0071] Performance Testing

[0072] The polyolefin composition for desiccant packaging prepared in the above embodiments and comparative examples was cast under a processing condition of 220-240°C, and a microporous network channel was formed inside the film by MDO stretching process to prepare a 30gsm breathable film; wherein the polyolefin breathable film composition was used to prepare a film sample in a temperature range of 220-240°C, with a stretching ratio of 3.0 times, a preheating temperature of 80°C, a stretching temperature of 90°C, and a setting temperature of 105°C.

[0073] Air permeability: According to GB / T 12704.2-2009 “Test method for water vapor permeability of textile fabrics”, the air permeability test temperature is 48℃ and the humidity is 50%RH.

[0074] Tensile properties: Tested according to ASTM D882-2018 standard.

[0075] Appearance: A film sample with a size of 20*100cm and a gram weight of 30gsm was prepared by the above-mentioned tape casting. The appearance of the film was observed under a light box. The grades are divided into 4 levels, with grade 1 being the best. Grade 4 means that there are serious bark patterns, and the bark patterns are densely distributed under the field of view of the light box; grade 3 means that there are obvious bark patterns, and the bark patterns are more under the field of view of the light box; grade 2 means that there are slight bark patterns, and the patterns are not obvious under the field of view of the light box; grade 1 means that there are no bark patterns and the product appearance is good.

[0076] In the application of desiccant bag breathable membrane products, the air permeability is required to be >3400g / m 2 ·24h, tensile strength> 4.0N, slight bark texture or no bark texture on the surface, that is, 1-2 levels meet the requirements.

[0077] Test results: as shown in Table 3.

[0078] Table 3

[0079]

[0080]

[0081] As can be seen from the above table, the air permeability of the polyolefin composition breathable film for desiccant packaging prepared in the embodiment of the present invention is greater than 3400g / m 2 ·24h, tensile strength> 4.0N, slight bark texture or no bark texture on the appearance, all meet the requirements.

[0082] From the comparison between Example 1, Example 8 and Comparative Examples 1-2, it can be seen that when the melt flow rate of the low-density polyethylene LDPE is 1-15 g / 10 min, the prepared polyolefin composition breathable film for desiccant packaging has good mechanical properties, high air permeability and good appearance.

[0083] From the comparison between Example 1, Example 9 and Comparative Example 3, it can be seen that the density of LLDPE is 0.93-0.95 g / cm 3 When the polyolefin composition breathable film for desiccant packaging is prepared, it has good mechanical properties, high air permeability and good appearance.

[0084] From the comparison of Example 1, Examples 10-12, and Comparative Examples 5-6, it can be seen that the weight ratio of the low-density polyethylene to the linear low-density polyethylene affects the air permeability, mechanical properties and appearance of the prepared polyolefin composition breathable film for desiccant packaging. When the weight ratio of the low-density polyethylene to the linear low-density polyethylene is 1:3-5, the mechanical properties or appearance of the prepared polyolefin composition breathable film for desiccant packaging is better.

[0085] From the comparison of Examples 1-7 and Comparative Examples 7-8, it can be seen that when the average particle size D50 of the heavy calcium carbonate is 4-7 microns, the prepared polyolefin composition breathable film for desiccant packaging has good mechanical properties, high air permeability and good appearance. When the heavy calcium carbonate is heavy calcium carbonate obtained by coating with a surface treatment agent, the appearance and mechanical properties of the prepared polyolefin composition for desiccant packaging are better. When the surface treatment agent is a phosphate ester, the air permeability can be better improved through interfacial adsorption, and the tensile strength of the film can be improved to a certain extent.

[0086] From the comparison of Example 1, Comparative Example 4 and Comparative Example 9, it can be seen that when HDPE exists in the polyolefin composition and the specific components and weight portions of LDPE and LLDPE of the present invention are not used, the air permeability of the breathable membrane is improved, but the mechanical properties are obviously deteriorated and appearance defects occur, which does not meet the requirements.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A polyolefin composition for desiccant packaging, characterized in that: The invention comprises the following components in parts by weight: 30-50 parts of polyolefin resin, 35-70 parts of heavy calcium carbonate, 0.5-2 parts of antioxidant, and 0.5-2 parts of processing aid; The polyolefin resin is a mixture of low-density polyethylene and linear low-density polyethylene in a weight ratio of (1-2): (3-6), wherein the low-density polyethylene has a melt flow rate of 1-15 g / 10 min at 190° C. and 2.16 kg according to ISO 1133-1-2011, and the density of the linear low-density polyethylene is 0.93-0.95 g / cm 3 ; The average particle size D50 of the heavy calcium carbonate is 4-7 microns.

2. The polyolefin composition for desiccant packaging according to claim 1, characterized in that: The linear low-density polyethylene has a melt flow rate of 0.5-2.0 g / 10 min at 190° C. and 2.16 kg according to ISO 1133-1-2011, and a density of 0.915-0.925 g / cm 3 .

3. The polyolefin composition for desiccant packaging according to claim 1, characterized in that: The heavy calcium carbonate is heavy calcium carbonate obtained by coating with a surface treatment agent, and the surface treatment agent is at least one of stearic acid, phosphate ester, titanate ester, and aluminate ester; preferably, the surface treatment agent is phosphate ester.

4. The polyolefin composition for desiccant packaging according to claim 1, characterized in that: The weight ratio of the low-density polyethylene to the linear low-density polyethylene is 1:3-5.

5. The polyolefin composition for desiccant packaging according to claim 1, characterized in that: The antioxidant is at least one of hindered phenols and phosphites, the processing aid is a lubricant, and the lubricant is at least one of fluorine-containing compounds, polyolefin waxes, low molecular esters, stearates, and amides.

6. A method for preparing the polyolefin composition for desiccant packaging according to any one of claims 1 to 5, characterized in that: The following steps are involved: After mixing the components in proportion, the components are melt-extruded and granulated to obtain the polyolefin composition for desiccant packaging.

7. Use of the polyolefin composition for desiccant packaging according to any one of claims 1 to 5 in the field of desiccant packaging.

8. The use according to claim 7, characterized in that The desiccant packaging field includes food desiccant packaging, daily necessities desiccant packaging, and clothing desiccant packaging.

Citation Information

Patent Citations

  • Breathable film composition special for warm paste, preparation method and application thereof

    CN112708190A

  • Special material for polyolefin breathable film as well as preparation method and application of special material

    CN112778600A

  • Special material for high-breathability and high-permeation-resistance polyolefin breathable film and preparation method and application thereof

    CN112795067A

  • PE breathable film material as well as preparation method and application thereof

    CN112852048A

  • Polyolefin breathable film composition as well as preparation method and application thereof

    CN114605736A

Cited By

  • High heavy calcium carbonate filled polyolefin master batch and preparation method thereof

    CN121086383A